A felicidade das pessoas idosas pode ser modificada pela disponibilidade de apoio social? - Zuccolotti, Laura Soares (Universidade Federal de São Carlos, 2025)
Common biopsychosocial changes and losses associated with aging can directly impact the mental health of older adults. In this context, social support acts as an important protective resource for perceptions of satisfaction, well-being, and happiness. Thus, this study aimed to verify whether there is a relationship between social support and happiness in older adults from the community treated at Family Health Units in the city of São Carlos. This is a descriptive, cross-sectional study based on the quantitative research method. Data were collected using the following instruments: Participant Sociodemographic Characterization Form, Medical Outcomes Study (MOS) Social Support Scale, and Subjective Happiness Scale. Descriptive and correlational analyses were performed. All ethical precepts regulating research with human beings were respected. The sample consisted of 95 elderly individuals, with a mean age of 69.80 years (SD = 6.90), 3.19 years of schooling (SD = 2.92) and individual and family incomes below 1.3 and 2.6 minimum wages, respectively. The participants were predominantly female (54.7%, n = 52), married (92.6%, n = 88), mixed race (49.5%, n = 47), Catholic (51.6%, n = 49), practicing a religion (74.7%, n = 71), retired (77.9%, n = 74) and with a perception of insufficient income (57.9%, n = 55). The elderly individuals had, on average, 13.05 close people (SD = 26.49). The average total score for social support was 81.35 points (SD=17.17) and the happiness score was 4.86 points (SD=1.05). The majority had intermediate happiness scores (61.1%, n=58). The results showed that there is a relationship between social support and happiness (p<0.05). Thus, it can be concluded that elderly people with greater availability of social support, a greater number of close friends and close people are happier.
Can the happiness of older people be modified by the availability of social support?
Keywords: Felicidade; Apoio social; Saúde mental; Pessoa idosa; CIENCIAS DA SAUDE